Transformasi Sistem Komunikasi Islam pada Generasi Z melalui Konten Dakwah Video Pendek - Muhammad Syafrizal; Mohd Rafiq (Lembaga Yasin AlSys, 2026)
Although Islamic communication has long served as an important framework for conveying da’wah messages, the development of digital media has significantly changed the way Generation Z receives, interprets, and responds to religious information. Various previous studies have discussed digital da’wah on social media, but studies that specifically examine the transformation of the Islamic communication system through short video content remain limited. This study aims to analyze changes in the Islamic communication system as a response to Generation Z’s consumption patterns in receiving da’wah messages through short video platforms. This study used a qualitative approach with a digital media analysis design. Data were collected through observation of short-form da’wah video content on digital platforms, audience interaction patterns, and documentation of Generation Z users’ communication behavior. The results showed that the Islamic communication process underwent significant transformation in the aspects of message packaging, media selection, audience attention span, and patterns of acceptance of religious authority. This transformation shows that the effectiveness of digital da’wah is determined not only by the substance of the message but also by the communicator’s ability to adapt the format, language, and delivery strategy to media characteristics and the communication behavior of young people. The conclusion of this study affirms the importance of adapting Islamic communication strategies to changes in Generation Z’s media consumption patterns in the digital era. These findings contribute to the development of contemporary Islamic communication studies and imply the need to strengthen digital da’wah literacy that is creative, concise, contextual, and continues to maintain the authority of Islamic scholarship.